1997
DOI: 10.1292/jvms.59.175
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bovine Prion Protein Gene: The Expression Requires Interaction between the Promoter and Intron.

Abstract: ABSTRACT. We cloned the part of the bovine PrP gene which contains the 5'-flanking region, exon 1, exon 2 and intron 1 to analyze its promoter region. The 5' non-coding region of the bovine PrP gene consisted of three exons and two introns, and its organization was similar to that of the mouse, rat and sheep PrP genes. The 5'-flanking region of the bovine PrP gene from the transcription start site to nucleotide position -88 was (G+C)-rich (78%) and contained three potential binding sites for the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 38 publications
8
73
0
Order By: Relevance
“…1). The available evidence suggests that polymorphisms in these regions affect transcription of the PRNP gene [15,18,21]. In a previous study, the 23-bp insertion was found to occur more frequently in healthy cattle than BSE-affected cattle [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1). The available evidence suggests that polymorphisms in these regions affect transcription of the PRNP gene [15,18,21]. In a previous study, the 23-bp insertion was found to occur more frequently in healthy cattle than BSE-affected cattle [28].…”
Section: Discussionmentioning
confidence: 93%
“…Among Holstein cattle in Japan, the 23-bp insertion has been found to have a lower allele frequency than the 23-bp deletion. We speculated that polymorphism of the 12-bp indel might affect expression levels of the PRNP gene, because the indel is in the promoter region of intron 1 and contains a putative Sp1-binding consensus sequence [9,15,18,19]. It has been reported that a GC-rich region and Sp1-binding sequence upstream of exon 1 are both important factors in PRNP transcription [1,15,18], but the effects of this Sp1 sequence in intron 1 are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that the low PrP C expression was due to inefficient expression of PrP mRNA. To address whether the low level of PrP gene expression is caused by genomic mutations in the regions involved in transcription of the PrP gene, we used long PCR to amplify the 5'-and 3'-flanking regions of exon 1 (nucleotides 6055-12058 in accession number U29186), which contain regions influencing PrP gene expression (17,33) and carried out a direct sequencing of the amplified products. We did not find any nucleotide differences in this region between authentic N2a cells and subclones N2a-5 and N2a-24.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of cell types expressing PrP c is necessary to understanding how the agent replicates and spreads from the periphery to the CNS. The mammalian Prnp gene has been described as a ubiquitous gene, with little known regarding gene regulation (26,31,32). The cellular specificity of the Prnp gene is based mainly on the data from PrP immunohistochemistry studies (14,16,33) and in situ hybridization (13,20,21,34).…”
Section: Discussionmentioning
confidence: 99%
“…A genomic library constructed in FIXII replacement vector (CLONTECH) was screened with a PCRamplified fragment corresponding to a previously sequenced region of 800 bp located upstream from the transcription initiation site of the bovine PrP gene (26). Two overlapping clones spanning Ϸ30 kb were isolated and analyzed.…”
Section: Methodsmentioning
confidence: 99%